Perencanaan Tebal Perkerasan dengan Metode Manual Desain Perkerasan Jalan 2024 (MDPJ 2024) dan Rencana Anggaran Biaya Studi Kasus di Ruas Jalan Muara Siau – Dusun Tuo Kabupaten Merangin - Engga Cendiago; Amsori M Das; Elvira Handayani (Universitas Batanghari Jambi, 2026)
The Muara Siau – Tuo Hamlet Road section in Merangin Regency which is a strategic connecting route that has an important role in community mobility and the distribution of agricultural and plantation products. The condition of the road has suffered severe damage such as cracks, holes and bumpy surfaces due to the presence of high-tonnage and repetitive plantation and sirtu transportation. The method used in rigid pavement planning is to use the 2024 road pavement design manual (MDPJ). This study aims to plan the thickness of road pavement and cost budget plan on the Muara Siau – Tuo Hamlet section. The results of this study were obtained with a thickness of 20 cm of class A foundation layer, 15 cm of thin concrete foundation layer, 25 cm of cement concrete pavement, the cost budget plan required is Rp. 6.896.250.084.